ECO-BASED REASONED ACTION MODEL: THE ROLE OF MANAGEMENT CONTROL SYSTEM - Sisdyani, Eka Ardhani (School of Accountancy, University of Agung Podomoro, 2020)
This paper aims to enrich Fishbein and Azjen’s Theory of Reasoned Action in predicting theemergence of green behavior by adding institutional-based control system to maintain greenintention’s stability. Intention’s stability is a crucial construct in realizing green behavior, though, itis affected by several instances such as: resources availability, individual capabilities, newinformation, and cooperation and commitment of individuals. For that reason, it is plausible to arguethat the existence of institutional-based control directing green behavior, such as eco-basedmanagement control systems, namely levers of eco-control, can maintain and augment one’s intentionto pursue green behavior. Thus, the paper contributes in enriching the knowledge of the emergenceand persistence of green behavior in organizations.